BMP3 inhibits TGFβ2-mediated myofibroblast differentiation during wound healing of the embryonic cornea - James W. Spurlin; Matthew R. Garis; Peter Y. Lwigale (npj Regenerative Medicine, 2022)
Abstract Often acute damage to the cornea initiates drastic tissue remodeling, resulting in fibrotic scarring that disrupts light transmission and precedes vision impairment. Very little is known about the factors that can mitigate fibrosis and promote scar-free cornea wound healing. We previously described transient myofibroblast differentiation during non-fibrotic repair in an embryonic cornea injury model. Here, we sought to elucidate the mechanistic regulation of myofibroblast differentiation during embryonic cornea wound healing. We found that alpha-smooth muscle actin (αSMA)-positive myofibroblasts are superficial and their presence inversely correlates with wound closure. Expression of TGFβ2 and nuclear localization of pSMAD2 were elevated during myofibroblast induction. BMP3 and BMP7 were localized in the corneal epithelium and corresponded with pSMAD1/5/8 activation and absence of myofibroblasts in the healing stroma. In vitro analyses with corneal fibroblasts revealed that BMP3 inhibits the persistence of TGFβ2-induced myofibroblasts by promoting disassembly of focal adhesions and αSMA fibers. This was confirmed by the expression of vinculin and pFAK. Together, these data highlight a mechanism to inhibit myofibroblast persistence during cornea wound repair.